Safety assessment of microwave ablation in sheep vertebral bodies - Hendricus Nijland; Jinwen Zhu; Thomas Kwee; Ding-Jun Hao; Paul Jutte (International Journal of Hyperthermia)
Background Spine is the most common location for bone metastases. Microwave ablation (MWA) is a technique for minimally invasive tumor treatment. The aim of the current study was to determine whether MWA is a safe option for treatment in vertebral bodies and to gain data on the amount of cortical insulation in the spine.Method MWA was applied with different settings for power and time in both in- and ex-vivo sheep vertebral bodies. Safety was evaluated by temperature measurements at critical surrounding structures (e.g. spinal cord, nerve root). Furthermore, the distribution of heat through the bone at 5 mm from the ablation needle was measured and compared to the temperature at the posterior wall.Results An effect of cortical insulation in the spine was found, for ablations with 20–30 and 50 W (p < 0.01). Ablations with wattage levels of 40–50 W almost instantly led to temperatures over 60 °C at the posterior wall. The temperature remained below 60 °C for 4 min in ex-vivo ablations with 20 and 30 W. However, in the in-vivo experiment paralysis was frequently seen (10/12 sheep) in lower wattages (20–30 W) as well and the experiment was therefore terminated.Conclusion MWA is an effective approach for local bone destruction in the spine. However, given the high risk of complications, caution is advised for treatment in vertebral bodies without better local distribution accuracy. Since cortical insulation appears insufficient to protect the spinal canal from excess heat, MWA involves a risk of paralysis.